Caste and Poverty Intertwined: The Livelihood Challenges Faced by Dalits in Makawanpur, Nepal - Budhathoki, Drona (International Research Journal of MMC, 2025)
The term Dalit refers to historically marginalized communities in Nepal who exist outside the traditional caste hierarchy. Derived from the Sanskrit word meaning "oppressed," it denotes groups formerly categorized as "untouchable" within the Hindu caste system. In Manahari, Makawanpur, rural Dalit populations continue to experience caste-based discrimination, limited economic opportunities, and restricted access to education. Despite the implementation of government policies aimed at inclusion, social exclusion remains pervasive, underscoring the need for more effective and targeted initiatives to enhance their livelihoods. This study aims to examine the livelihood challenges faced by the Dalit community in Ward No. 5, Basantpur, of Manahari Rural Municipality. Employing a descriptive research design, data were collected from 35 Dalit households through interviews and participant observation. Primary data were gathered using a census approach and supplemented with secondary data drawn from existing literature, including books and academic journals. Findings reveal entrenched economic, social, and political inequalities. Although Nepal has transitioned toward capitalism, Dalits continue to encounter limited economic opportunities, low political representation, and persistent poverty. Contributing factors include lack of land ownership, inadequate access to education, and exclusion from skilled employment. Addressing these systemic challenges necessitates reforms in land distribution, educational access, and political empowerment to ensure equitable opportunities for marginalized groups. The significance of this study lies in its focus on the socio-economic hardships faced by Dalits in rural Manahari. It brings attention to critical issues such as restricted access to education, healthcare, and employment challenges that are largely the result of systemic caste-based discrimination. The research aims to inform policy development that advances social justice, equality, and inclusion, with a particular emphasis on mitigating caste-based inequalities and poverty.